2006
DOI: 10.1096/fj.05-4828com
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatic fibrogenesis by matrix metalloproteinase‐9 mutants in mice

Abstract: Tissue inhibitor of metalloproteinases-1 (TIMP-1) plays a crucial role in the pathogenesis of hepatic fibrosis and thus may represent an important therapeutic target in the design of anti-fibrotic strategies for chronic liver disease. We present an innovative therapy based on the assignment of inactivated enzymes acting as scavengers for TIMP-1. Hepatic fibrosis was induced in BALB/c mice by repetitive intraperitoneal CCl4 injection. The animals were treated with proteolytic inactive matrix metalloproteinase-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 61 publications
2
119
0
Order By: Relevance
“…180 Conversely, the use of MMP-9 mutant proteins as TIMP-1 scavengers reduces fibrosis accumulation by enhancing matrix resorption. 181 Stellate cells express uroplasminogen activator receptor and its inhibitor, as well as other components of the plasmin system. [182][183][184] Collectively, these findings suggest that stellate cells contain most, if not all, of the molecules necessary to either activate or inhibit metalloproteinases.…”
Section: Matrix Degradation and Resolution Of Fibrosismentioning
confidence: 99%
“…180 Conversely, the use of MMP-9 mutant proteins as TIMP-1 scavengers reduces fibrosis accumulation by enhancing matrix resorption. 181 Stellate cells express uroplasminogen activator receptor and its inhibitor, as well as other components of the plasmin system. [182][183][184] Collectively, these findings suggest that stellate cells contain most, if not all, of the molecules necessary to either activate or inhibit metalloproteinases.…”
Section: Matrix Degradation and Resolution Of Fibrosismentioning
confidence: 99%
“…Another yet preclinical strategy is to block TIMP-1, a major effector of liver fibrosis, by use of a recombinant mutant protein derived from its high-affinity ligand MMP-9. 48 An intriguing novel target is the integrin ␣v␤6, a cell surface receptor that is expressed on activated epithelia during embryogenesis, wound healing, and tumorigenesis. 49 ␣v␤6 anchors these epithelia to a provisional ECM of tenascin and fibronectin 17 and through tethering latent TGF␤1 promotes its proteolytic activation.…”
Section: Antifibrotic Drug Developmentmentioning
confidence: 99%
“…40,41 Furthermore, the mutation of MMP-9 was reported to inhibit hepatic fibrogenesis in mice. 42 This study showed that MMP-9 and TNF-a mRNA expression increased significantly with the activation of Kupffer cells that were positive for CD68 in group M, whereas switching the diet from MCDD to CD triggered the immediate recovery of MMP-9, suggesting that MMP-9 is associated with the activation status of Kupffer cells.…”
Section: Discussionmentioning
confidence: 60%